UPPER LIMB JOINTS AND MOTIONS SAMPLING SYSTEM USING KINECT CAMERA - Albawab, T.M.M.; Halim, I.; Ahmad, N.; Umar, R.Z.R.; Mohamed, M.S.S.; Abullais, F.; Basari, A.S.H.; Bakar, M.; Saptari, A. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The needs of research on human posture and its joint-motion relationships are important. Providing a real-time postural measurement tool has attracted the attention of many human postural-related researchers. This study has developed and performed a validation analysis on a new innovative system for sampling and finding the angles of motions of each posture with its related joints using Kinect camera. The validation investigated the static and dynamic accuracy analyses by comparing to a Jamar goniometer and ErgoFellow system. The results showed that Mean Absolute Errors of Kinect in static and dynamic motions are 15.12% and 45.33% respectively. It is concluded that the postural measurement system developed by this study requires further improvements.